Fine-Scale Plant Richness Mapping of the Andean Páramo According to Macroclimate - Peyre, Gwendolyn; Balslev, Henrik; Font, Xavier; Tello, J. Sebastián (Frontiers in Ecology and Evolution, 2019)
Understanding the main relationships between the current macroclimate and broad spatial patterns of plant diversity is a priority in biogeography, and although there is an important body of studies on the topic worldwide, tropical mountains remain underrepresented. Because understanding primary drivers of diversity patterns in the Andean páramo is still in its infancy, we focused on evaluating the role of the current macroclimate in form of three complementary hypotheses, energy, seasonality and harshness, in explaining local variation of plant species richness. We relied on 1,559 vegetation plots that offered a fine-scale outlook on real species assemblages due to community rules and species' interactions with their surrounding environment, including climate. Generalized Least Squares (GLS) regression models provided insight on the significance of the different hypotheses in explaining local plant richness, but only the energy and seasonality hypotheses received partial support. The best model was then combined with spatial interpolation Kriging modeling techniques to project species richness for a standardized 25 m2 plot throughout the entire páramo biogeographical province. We highlighted a North-South increase in richness with several species-rich areas, potential local biodiversity hotspots, independent of the general gradient: the Amotape-Huancabamba zone, Sangay and Cotacachi areas, and eastern Venezuelan Andes. Our endeavor to finely map local richness is the first effort predicting macroecological patterns in the emblematic Andean páramo and contributes novel biogeographical knowledge useful to further support in-depth research and conservation focus in the northern Andes.